2022
DOI: 10.21203/rs.3.rs-2273694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serial Viral Load Analysis by Ddpcr to Evaluate Fnc Efficacy and Safety in the Treatment of Mild Cases of Covid-19

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has threatened the human population globally as the numbers of reinfection cases even after large-scale vaccination. Trials have been carried out to find drugs effective in fighting the disease, as COVID-19 is being considered a treatable disease only after we have antivirals. A clinical candidate originally developed for HIV treatment, AZVUDINE (FNC), is a promising drug in the treatment of COVID-19, being able to reduce the patient's v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In phase III clinical trial (trial number: NCT05033145), mild COVID-19 patients who received Azvudine treatment experienced a shorter NANC by an average of 2.7 d compared to those in the placebo group. [34] Compared to placebo groups, Azvudine showed good safety. The adverse reactions included headache, dizziness, AST increase, nausea, ALT increase, and D Dimer increase and were the same as those related to antiviral drugs.…”
Section: Clinical Studies Of Azvudine For Covid-19 Treatmentmentioning
confidence: 96%
“…In phase III clinical trial (trial number: NCT05033145), mild COVID-19 patients who received Azvudine treatment experienced a shorter NANC by an average of 2.7 d compared to those in the placebo group. [34] Compared to placebo groups, Azvudine showed good safety. The adverse reactions included headache, dizziness, AST increase, nausea, ALT increase, and D Dimer increase and were the same as those related to antiviral drugs.…”
Section: Clinical Studies Of Azvudine For Covid-19 Treatmentmentioning
confidence: 96%
“…The results were detailedly disclosed in the preprints published on the Research Square platform (https://www.researchsquare.com), and showed that Azvudine significantly reduced the time of nucleic acid negative conversion (NANC) as well as the viral load of the patients compared to placebo. 4,5 Taken together, Azvudine could decrease the time of NANC, viral load, and median time to improvement in clinical condition, and increase the proportion of improvement in clinical condition on day 7 in the patients with COVID-19. In addition, Azvudine exhibited good safety and well tolerance as compared to placebo.…”
mentioning
confidence: 99%